Openness and Technological Innovations in Developing Countries : Evidence from Firm-Level Surveys - Almeida, Rita; Fernandes, Ana Margarida (World Bank, Washington, DC, 2012)
The authors analyze the role of international technological diffusion for firm-level technological innovations in several developing countries. Their findings show that, after controlling for firm, industry, and country characteristics, exporting and importing activities are important channels for the diffusion of technology. They also find evidence that the majority of foreign-owned firms are significantly less likely to engage in technological innovations than minority foreign-owned firms or domestic-owned firms. The authors interpret this finding as evidence that the technology transferred from multinational parents to majority-owned subsidiaries is more mature than that transferred to minority-owned subsidiaries. This finding supports the idea that equity joint ventures maximize technology transfers to local firms.